Collaborating to stay open and aware: Service user involvement in mental health research as an aid in reflexivity. Issue 4 (2nd October 2017) - Veseth, Marius; Binder, Per-Einar; Borg, Marit; Davidson, Larry
Abstract: Research collaboration with people with first-hand knowledge of mental distress and recovery processes has been argued to hold potential of making studies more relevant and more rigorous. There is, however, less awareness of how service user involvement can increase reflexivity in research, which is another important component to evaluating the quality of studies. In this conceptual analysis, we explore our experiences of doing collaborative research and discuss these in relation to the concept of reflexivity. We argue that both in planning investigations, collecting the material as well as in data analytic phases, partnering up with service users can be a valuable way to stay open and aware in the process of conducting qualitative studies on issues in mental health. We identify reflexivity as a possible benefit of service user involvement in research and as crucial for actualizing the full potential of such research collaborations.